Association between fear of falling and falls following acute and chronic stroke: a systematic review with meta-analysis - Tamis W. Pin; Stanley J. Winser; Wayne L.S. Chan; Bolton Chau; Shamay Ng; Thomson Wong; Margaret Mak; Marco Pang (Journal of Rehabilitation Medicine, 2024)
Objectives: To examine the association between falls and fear of falling in people with stroke and to evaluate the differences between patients with acute stroke and those with chronic stroke with regard to any such association.